Pelindungan Hukum bagi Bidan Memberikan Pelayanan Obat kepada pasien dalam Praktik Kebidanan di Daerah Terpencil - Asyah, Nur (Jurnal Hukum dan Etika Kesehatan, 2024)
Midwives are health workers who have been recognized as stated in Law Number 17 of 2023 concerning Health. A midwife's professionalism is determined if she can work according to her function and role based on the authority that has been determined. Midwives' authority to administer medication is limited by regulation. However, midwives who work in remote areas are often faced with problems regarding their authority to administer medication to patients. When in remote areas, midwives provide medicine to patients according to the patient's problem or illness based on the patient's needs. The purpose of this writing is to analyze the authority of midwives to provide drug services to patients in midwifery practice and examine the form of legal protection for midwives in carrying out practice. The author uses a research method with a normative juridical type and approaches the problem using legislation, a conceptual approach and a comparative approach.The results of this research are Legal protection for midwivesproviding medicinal services to patients in midwifery practice in remote areas is regulated in Article 273 of the Health Law which states that: "personnel in carrying out practice have the right to obtain legal protection as long as they carry out their duties in accordance with professional standards, professional service standards and standard operational procedures and professional ethics, as well as patient health needs. Likewise, Article 19 of the Minister of Health's Permit and Practice of Midwives also states that "in carrying out practice/work, midwives have the right to obtain legal protection in carrying out practice/work as long as they comply with standards."